A study of Consumer Awareness for Green Marketing - Manjunatha M. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
In current business scenario environmental issues plays an important role in business. In most of the countries government is concerned about the environmental problems. In today’s business environmentally sustainable development has become a key issue. Thus Green marketing is one of the strategies a firm can adopt to achieve this. Green Marketing refers to the process of selling products and /or services based on their environmental benefits. Such a product or service should be eco-friendly in itself or produced in an eco-friendly way. In today’s environmentally conscious world the word “Green” has become a buzz word. Green causes are increasingly popular with public making green marketing good for public relations and sales. Green Marketing has been defined by AMA as “The study of the positive and negative aspects of marketing activities on pollution, energy depletion and non-energy resource depletion”. However one of the basic assumptions of green marketing is that potential consumers would be willing to pay more for a “green” product. The present paper makes an attempt to analyse the awareness and willingness of the consumer to buy green products.